Contribution to the Chinese subfamily Rhaphidophorinae Walker, 1869 (Orthoptera: Rhaphidophoridae) V: Two new species of Eurhaphidophora - Lu, Xiangyi; Huang, Xiaojuan; Bian, Xun (Zootaxa, 2022)
This paper describes two new species of Eurhaphidophora, namely: Eurhaphidophora curvata sp. nov. (Chinese name: 弯板优驼螽) and Eurhaphidophora fossa sp. nov. (Chinese name: 凹板优驼螽) based on the specimens from Yunnan Province, China. The type specimens are deposited in the Guangxi Normal University, Guilin, China.